Interregional Circulation in the Calchaquí Valley (Province of Salta, Northwestern Argentina): a Comprehensive View from New and Old Evidence - Sprovieri, Marina (Revista Española de Antropología Americana, 2015)
This work presents the results of the systematic study concerning the circulation of goods, raw materials and ideas in the Calchaquí Valley (Province of Salta, Northwestern Argentina) between the 10th and 16th centuries. Through stylistic and provenance analyses of various materials from museums’ archaeological collections, it was possible to establish the diversity of goods and materials that circulated to and from the valley in different moments of its occupational history. These new findings were considered in relation to already existing information about interregional connections for the Calchaquí societies, and the existence of several potential interaction circuits with different ecological and cultural areas was postulated. Such circuits apparently show certain changes since the Inka arrival to the Calchaquí Valley.